Nose-Driven Cursor Control: An Assistive System for Disabled Individuals Using OCRM Similarity Tracking - 1Gnaneswara Rao Nitta; Sai Likhitha Alapati; Sneha Nitta,4Hari Prasada Raju (The Bioscan, 2024)
This paper introduces a visual mouse system designed to assist disabled individuals in controlling computer mouse functions, such as cursor movement and clicking actions, using simple body gestures. Specifically, the system tracks the user’s nose tip to execute mouse commands, providing an untouchable alternative for desktop interaction. The main goal is to create an accessible, low-cost solution using widely available hardware to make computing more inclusive for individuals with physical disabilities. Using a camera, the system captures and translates user head movements into mouse gestures on the screen. The proposed methodology is built around visual tracking, isolating a sample region from each video frame and then identifying that region in subsequent frames through Optimal Cost Region Matching (OCRM). This similarity measure ensures accurate and seamless tracking of the user's movement, providing an effective control mechanism. Experimental results demonstrate that the OCRM-based visual mouse system outperforms existing Camera Mouse applications regarding reliability and efficiency. The proposed approach delivers a flexible, cost-effective, and consistent solution for enhancing computer accessibility for disabled users.